PENGEMBANGAN TRAINING KIT ENGINE MANAGEMENT SYSTEM TOYOTA AVANZA K3-VE UNTUK PRAKTIKUM OTOMOTIF - Handoyono, Nurcholish Arifin; Rabiman, Rabiman (Jurnal Pendidikan Vokasi Otomotif, 2023)
The research aims to determine: (1) The process of developing the Toyota Avanza K3-VE engine management system training kit; (2) Feasibility of the developed Toyota Avanza K3-VE engine management system training kit; and (3) The effectiveness of the developed Toyota Avanza K3-VE engine management system training kit. The type of research used is development research using a 4-D model. The research subjects consisted of 20 students, while the research object was the Toyota Avanza K3-VE engine management system training kit. Data collection uses observation, questionnaires and tests. Data were analyzed descriptively qualitatively, quantitatively, and inferentially using gain test statistics. The research results show that: (1) The process of developing the Toyota Avanza K3-VE engine management system training kit with the 4-D model includes 4 stages, namely define, design, develop and disseminate; (2) The feasibility test of the Toyota Avanza K3-VE engine management system training kit obtained very good results with details of the average results from media experts at 88.75%, from material experts at 92.50%, from lecturers at 92.50 %, from small group trials 86%, and from large group trials 87.75%; and (3) The effectiveness test results show that the Toyota Avanza K3-VE engine management system training kit developed is effective for use in lectures with an N-gain result of 0.62.